Rimegepant - a breakthrough drug for migraine treatment - literature review - Kuleta, Katarzyna; Głoskowska, Julia; Frańczuk, Agata; Grzelka, Michalina; Makłowicz, Aleksandra; Kopczyńska, Ewelina; Szpulak, Angelika; Karkos, Patrycja; Kuśmierczyk, Katarzyna; Dolata, Natalia (Quality in Sport, 2024)
Migraine is a chronic condition that manifests itself periodically. It is characterized by recurrent, severe, often hemiplegic, throbbing headaches accompanied by autonomic symptoms in the form of nausea, vomiting, hypersensitivity to noise and light. For many years, triptans have been the gold standard in the treatment of migraine, acting by constricting blood vessels and inhibiting the release of neuropeptides. However, their efficacy is not satisfactory for all patients, especially those with cardiovascular disease. In response to the need for effective and safe therapies, gepants, a new class of drugs that block the calcitonin gene-related peptide (CGRP) receptor, have emerged. Rimegepant, one of the newest representatives of gepant, has been approved for the treatment of migraine both in the acute attack phase and prophylactically. Clinical trials have shown its effectiveness in reducing the number of days with migraine and alleviating associated symptoms. Rimegepant also has a favorable safety profile, making it a promising therapeutic option for migraine patients. This article aims to discuss in detail rimegepant as a new treatment option for migraine, including its mechanism of action, efficacy, safety profile, clinical trial and outlines the benefits of introducing this drug into standard clinical practice.